A Qualitative Study of Consumers' Experiences of the Quality of Mental Health Services in Ghana. (17th February 2022) - Badu, Eric; O'Brien, Anthony Paul; Mitchell, Rebecca; Osei, Akwasi
Abstract: Integrating consumers' experiences into quality mental health service assessment is relevant to improve service outcomes. Despite this, limited studies have attempted to explore consumers' experiences, particularly in developing countries, such as Ghana. This paper aims to explore consumers' subjective experiences of the quality of mental health services. A qualitative method involving in-depth interviews was used to collect data from 21 consumers of mental health services. Thematic analysis was used to analyse the data, which is discussed using a realistic evaluation approach. The study identifies four themes, 33 inductive codes and 594 references. The themes used to interpret the verbatim narratives are the available mental health services, therapeutic interaction with the professionals, competency and skills of the professionals, and the changes experienced in the consumers' lives. The study indicates that the mental health services aim to provide a range of treatments and medications as well as recovery-oriented services, using mechanisms such as ensuring an effective therapeutic relationship and improving technical competency and skills. The contextual factors and the mechanisms have helped to achieve some changes in the lives of consumers (increased satisfaction, reduced symptoms, improved functionality, feeling normal, improved living skills and self-care, work and capabilities, and social inclusion). The study concludes that policymakers and clinicians should integrate evidence-based recovery services, principles and values into the existing mental health services. The mechanisms used to promote quality of mental health services should be strengthened, through periodic monitoring and evaluation, using approaches such as sensor data capturing, to ensure good coordination and continuity.